2007
DOI: 10.1002/jso.20754
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to accurately position Port‐A‐Cath without the aid of intraoperative fluoroscopy or other localizing devices

Abstract: The modified method for inserting the PAC offered the following benefits: including avoiding X-ray exposure for both the operator and the patient, defining the appropriate position in the SVC, and less surgical time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…At present, the radiologically assisted percutaneous approach is preferred to the traditional surgical approach, due to its technical success rate, and safety and reduced morbidity [9, 10]. Some investigators have reported that PAC devices can be placed safely without the aid of catheter‐localizing devices or intraoperative imaging in order to reduce cost and surgical time [11, 12]; however, UK guidelines for the placement of central venous catheters (CVCs) recommend that an ultrasound‐guided technique should be adopted as it is associated with a reduced incidence of complications [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the radiologically assisted percutaneous approach is preferred to the traditional surgical approach, due to its technical success rate, and safety and reduced morbidity [9, 10]. Some investigators have reported that PAC devices can be placed safely without the aid of catheter‐localizing devices or intraoperative imaging in order to reduce cost and surgical time [11, 12]; however, UK guidelines for the placement of central venous catheters (CVCs) recommend that an ultrasound‐guided technique should be adopted as it is associated with a reduced incidence of complications [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…The actual puncture site and the angulation curvature might lead to the difficulty for measurement for inexperienced operators. Triggering arrhythmia has been proposed as alternate way to confirm the tip position 13. Short‐run atrial premature complex or ventricular premature complex is usually tolerable, but for critically ill patients, it is better avoided.…”
Section: Discussionmentioning
confidence: 99%